Adaptive and optimum multiport readout of non-gated crossbar memory arrays. (September 2017) - Emara, Ahmed A.M.; Aboudina, Mohamed M.; Fahmy, Hossam A.H.
Abstract: Non-gated crossbar memory arrays are becoming strong candidates to replace the current gated arrays due to their much higher density. Sneak paths are the main problem in gate-less arrays. In this paper, we analyze a three reading multiport readout method for non-gated memory arrays, study its limitation versus the OFF/ON impedance ratio of the memory cell as well as the ratio between the 1 s and 0 s memory cells. We provide an accurate threshold that increases the noise margins that takes these factors into consideration and we also introduce an adaptive threshold that tracks the 1 s and 0 s density variations over time. Finally, we propose a sensing circuit that accumulates the three reading without the need for extra complicated circuitry to evaluate the read memory cell value.